A Subclass of Analytic Functions Related to k-Uniformly Convex and Starlike Functions. (23rd May 2017) - Hussain, Saqib; Rasheed, Akhter; Zaighum, Muhammad Asad; Darus, Maslina
Abstract : We investigate some subclasses of k -uniformly convex and k -uniformly starlike functions in open unit disc, which is generalization of class of convex and starlike functions. Some coefficient inequalities, a distortion theorem, the radii of close-to-convexity, and starlikeness and convexity for these classes of functions are studied. The behavior of these classes under a certain modified convolution operator is also discussed.